BLOOD PRESSURE MEASURING DEVICE EMBEDDED WITH SMS CAPABILITIES - Anuar, Siti Hajar binti (UNIVERSITI TEKNOLOGI PETRONAS, 2009)
For a high blood pressure patient, checking their blood pressure at home is an important part in managing high blood pressure (hypertension). It is recommended that anyone with high blood pressure to monitor their blood pressure at home. This home monitoring can help them keep tabs on their blood pressure in a familiar setting, make certain their medication is working, and alert the patient and the doctors to potential health complications. Doctors can use the measurements to see how well the medicine is working to control the high blood pressure. The current blood pressure measuring device in the market has the functions to display the blood pressure, heart beat rate and save the obtained data in the device memory. But so far, there is no development yet to this device where these obtained data can be sent to other people for records. Thus, this project presents the development of a blood pressure measuring device that is embedded with SMS capabilities.